A Novel Large Animal Model of Thrombogenic Coronary Microembolization - Bikou, Olympia; Tharakan, Serena; Yamada, Kelly P.; Kariya, Taro; Gordon, Alexandra; Miyashita, Satoshi; Watanabe, Shin; Sassi, Yassine; Fish, Kenneth; Ishikawa, Kiyotake (Frontiers in Cardiovascular Medicine, 2019)
Coronary microembolization is one of the main causes of the “no-reflow” phenomenon, which commonly occurs after reperfusion of an occluded coronary artery. Given its high incidence and the fact that it has been proven to be an independent predictor of cardiac morbidity and mortality, there is an imperative need to study its underlying mechanisms and pathophysiology. Large animal models are essential to perform translational studies. Currently there is no animal model that recapitulates a clinical scenario of thrombogenic microembolism with preceding myocardial ischemia. Therefore, the goal of this study was to develop and characterize a novel pig model of coronary microembolization using autologous thrombus injection (CMET). Twenty-three pigs underwent myocardial infarction through percutaneous balloon occlusion of the left anterior descending artery (LAD). Each animal was enrolled in one of two groups: (1) the CMET group, in which the LAD occlusion was followed by delivery of autologous clotted blood in the LAD (distal to the balloon occlusion) and reperfusion; (2) the ischemic reperfusion (I/R) group, in which the LAD ischemia was followed by reperfusion. Surviving animals underwent functional and morphological characterization at 1-week post-procedure. Three sham operated animals were used as a control. CMET resulted in impaired left ventricular function compared to I/R pigs at 1 week. Three-dimensional echocardiography demonstrated reduced ejection fraction in the CMET group (CMET vs I/R: 35.6 ± 4.2% vs 47.6 ± 2.4%, p=0.028). Invasive hemodynamic measurements by Swan-Ganz and left ventricular pressure-volume catheters revealed that CMET impaired left ventricular contractility and diastolic function. This was confirmed by both load dependent indices including cardiac output (CMET vs I/R: 2.7 ± 0.2 l/min, vs 4.0 ± 0.1 l/min, p<0.001) and load independent indices including preload-recruitable stroke work (CMET vs I/R: 25.8 ± 4.0 vs 47.5 ± 6.5 mmHg, p=0.04) and end-diastolic pressure-volume relationship (slope, 0.68 ± 0.07 mmHg/ml, vs 0.40 ± 0.11 mmHg/ml, p=0.04). Our unique closed-chest model of coronary microembolization using autologous thrombus injection resembles the clinical condition of thrombogenic coronary microembolization in I/R injury. This model offers opportunities to conduct translational studies for understanding and treating coronary microembolization in myocardial infarction.